Increased hippocampal engagement during learning as a marker of sensitivity to psychotomimetic effects of δ-9-THC. Issue 16 (5th March 2018) - Bhattacharyya, Sagnik; Sainsbury, Thomas; Allen, Paul; Nosarti, Chiara; Atakan, Zerrin; Giampietro, Vincent; Brammer, Michael; McGuire, P K
Abstract: Background: Cannabis and its main psychoactive ingredient δ -9-tetrahydrocannibidiol (THC) can induce transient psychotic symptoms in healthy individuals and exacerbate them in those with established psychosis. However, not everyone experience these effects, suggesting that certain individuals are particularly susceptible. The neural basis of this sensitivity to the psychotomimetic effects of THC is unclear. Methods: We investigated whether individuals who are sensitive to the psychotomimetic effects of THC (TP) under experimental conditions would show differential hippocampal activation compared with those who are not (NP). We studied 36 healthy males under identical conditions under the influence of placebo or THC (10 mg) given orally, on two separate occasions, in a pseudo-randomized, double-blind, repeated measures, within-subject, cross-over design, using psychopathological assessments and functional MRI while they performed a verbal learning task. They were classified into those who experienced transient psychotic symptoms (TP; n = 14) following THC administration and those who did not (NP; n = 22). Results: Under placebo conditions, there was significantly greater engagement of the left hippocampus ( p < 0.001) in the TP group compared with the NP group during verbal encoding, which survived leave-one-out analysis. The level of hippocampal activation was directly correlated (Spearman's ρ = 0.44, p = 0.008) with the severity of transient psychotic symptoms induced by THC. This difference was not present when we compared two subgroups from the same sample that were defined by sensitivity to anxiogenic effects of THC. Conclusions: These results suggest that altered hippocampal activation during verbal encoding may serve as a marker of sensitivity to the acute psychotomimetic effects of THC.